Intrinsic and Extrinsic Work Values and Organizational Commitment Among Employees of Um Tagum College - Nikki Jane V. Arsenal; Raiza Mae Calbonero Narciso; Daven Dela Rama; Crisamay F. Tabigue (LPPM of NAROTAMA UNIVERSITY, 2021)
The main goal of this study was to determine if there is a significant relationship between work values and organizational commitment among employees of UM Tagum College using quantitative non-experimental research design utilizing correlational technique with 106 employees of UM Tagum College using purposive sampling technique in determining the respondents. Mean and Pearson (r) were the statistical tools used for data treatment. Results showed a very high level of both intrinsic and extrinsic work values among employees of UM Tagum College. Moreover, high level of organizational commitment was attributed among employees of UM Tagum College. Lastly, the result further showed that intrinsic work values and extrinsic work values have significant relationship with organizational commitment among employees of UM Tagum College.